Hubungan antara Mekanisme Koping dengan Tingkat Kecemasan pada Pasien Preoperasi Debridement - Helin Narwiyati (STIKES Widyagama Husada, 2026)
A wound is damage to part of the body's tissue caused by trauma from sharp or blunt objects and others due to loss of continuity of epithelial tissue with or without damage to other tissues. The debridement action plan for preoperative patients is a psychosocial stressor that causes anxiety in patients who will undergo it, so the role of coping mechanisms is very important for patients to control the anxiety they experience. The purpose of this study was to determine the Relationship Between Coping Mechanisms and Anxiety Levels in Preoperative Debridement Patients in the Emergency Room of Dr. Saiful Anwar Hospital, East Java Province. The design used in this study was Cross Sectional. Sampling using purposive sampling with a sample of 92 pre-operative patient respondents. Based on the results of the study, it showed that respondents aged 26-45 years were 49 respondents (53%), male gender was 47 respondents (51.1%), high school education was 54 respondents (58.7%), adaptive coping mechanisms were 56 respondents (60.9%), moderate anxiety levels were 33 respondents (35.9%). From the results of the Spearman Rho bivariate statistical test, the Sig. value was 0.008 <0.05, which means that there is a significant relationship between coping mechanisms and anxiety levels in pre-operative debridement patients. Feelings of discomfort, stress and worry in pre-op debridement patients are influenced by several different factors in each individual, including the coping mechanisms they have. It is hoped that these feelings of discomfort can subside soon, and patients can learn to adapt to any changes that occur. Keywords: Debridement; Anxiety; Coping Mechanisms.